Proceedings of the 11th International Conference on Vacuum Ultraviolet Radiation Physics : Tokyo, Japan, 27 August-1 September 1995. - Miyahara, T. (Tsuneaki) (Elsevier Science B.V., 1996)
These volumes contain 365 of the 505 papers presented at the VUV-11 Conference, held at Rikkyo University, Tokyo, from August 27th to September 1st 1995. The papers are divided into three sections: atomic and molecular spectroscopy, solid state spectroscopy and instrumentation and technological applications. New aspects presented were both quantitative and qualitative improvements in fluorescence spectroscopy and magnetic circular dichroism measurements. The fluorescence data are complementary to those of photoemission in a sense but they appear to open up a new method to analyze the optical excitation and relaxation processes. The application of magnetic circular dichroism has proved to be useful not only in analyzing the electronic structures of magnetic materials but also in practical applications to material engineering as found in experiments combined with photoelectron microscopy. Excellent developments in applications are only found in the field of surface photochemistry, where the technique of etching using VUV light has been appreciably refined. Although the majority of distinctive scientific features in the VUV-11 Conference have been brought about by the application of synchrotron radiation, experiments using a different type of light source appear to have progressed steadily. This is evident in the studies of plasma radiation.